Aplicação da framework NSDL para a descrição de cenários de redes openflow - SOUZA, Lucas Lucian Borges de (2014)
The constant technological evolution and development of telecommunication lead to the proposal of new equipment, standards and protocols for communication networks. Therefore, it is important to provide more dynamic and realistic, testing environments where the current experiments are not allowed to interfere in the operational network. Nevertheless, the implementation of these experiments can be a very complex activity, for this reason, in order to allow the experimentation of new protocols in computer networks, the paradigm of programmable virtualized networks (so-called Software-Defined Networks) has been proposed. OpenFlow is one of the proposals for the implementation of Software-Defined Networks. The main goal of OpenFlow is to allow an experiment to be executed in a real network allowing reprogramming the switches so that they can handle the traffic from the experiments without interfering in the operation of the production network. Currently there are different tools and approaches for the implementation and monitoring of OpenFlow experiments. From this perspective, there is also the need of proposals that allow the integrated management of these networks providing the interoperability between these tools. One possible solution is the adoption of the NSDL Framework (Network Scenarios Description Language), which has been proposed at University of Madeira (Portugal) to provide interoperability between different tools for network management. This Framework is based on a common language (also called NSDL) that allows the description of the network scenarios that can be exchanged between different tools. The network Scenarios allow textually or graphically to represent a network topology, that is, all the network components: computers, routers, protocols, traffic information, etc. It also includes a description of the objects and their network parameters in a given context. The main goal of this work is the proposal of an extension to NSDL in order to support the description of OpenFlow scenarios. The contribution of this work was enabled by the study and analysis of Software-Defined Networks, which allowed the identification of functional and non-functional requirements. Further on, the proposed language was also validated by the implementation of some case studies.